2020
DOI: 10.3390/ma13204601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sand Fines Concentration on the Erosion-Corrosion Mechanism of Carbon Steel 90° Elbow Pipe in Slug Flow

Abstract: Erosion-corrosion of elbow configurations has recently been a momentous concern in hydrocarbon processing and transportation industries. The carbon steel 90° elbows are susceptible to the erosion-corrosion during the multiphase flow, peculiarly for erosive slug flows. This paper studies the erosion-corrosion performance of 90° elbows at slug flow conditions for impact with 2, 5, and 10 wt.% sand fines concentrations on AISI 1018 carbon steel exploiting quantitative and qualitative analyses. The worn surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The maximum Ra value was observed between 45° and 90° axial angles at the upper and bottom half of the 90° elbows. Hence, it was concluded that carbon steel 90° elbow showed maximum erosion behavior near the outlet, as mentioned in the literature [ 17 ]. On the other hand, the Ra of the samples was maximum in the outer wall in both the top and bottom of the elbow pipe.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The maximum Ra value was observed between 45° and 90° axial angles at the upper and bottom half of the 90° elbows. Hence, it was concluded that carbon steel 90° elbow showed maximum erosion behavior near the outlet, as mentioned in the literature [ 17 ]. On the other hand, the Ra of the samples was maximum in the outer wall in both the top and bottom of the elbow pipe.…”
Section: Resultsmentioning
confidence: 89%
“…The device used to acquire surface roughness parameters was Mitutoyo SURFTEST SJ-210. Details about the testing procedure were published in our previous work [ 17 , 18 ].…”
Section: Experiments Procedures and Test Methodsmentioning
confidence: 99%
“…The investigation results suggest that the cause of failure is electrochemical corrosion combined with the mechanical process, known as flow-induced corrosion [11]. Gathering pipelines in oilfields are seriously damaged by erosion-corrosion, which results from media including oil, gas, water and sand grains in the brine [12], so it is multiphase flow erosion-corrosion [13,14]. Because of the various compositions of oilfield brines, the mechanism of multiphase flow corrosion-erosion on the inner wall of gathering pipelines is very complex and not clear [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Erosive wear is generally undesirable because it can cause significant material disintegr ation, which further leads to the malfunction of piping components i.e. elbows and tee junctions [1][2][3]. There are numerous kinds of erodent amenable for erosive wear in hydrocarbon, chemical, and minerals processing industries.…”
Section: Introductionmentioning
confidence: 99%